U.S. BITs and financial stability - Kevin P. Gallagher (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2010)
The author, a member of the State Department subcommittee tasked with reviewing the U.S. Model bilateral investment treaty, addresses the potential impact of BIT provisions on the ability of governments to prevent and mitigate financial crises and makes specific recommendations for the revised Model BIT.
Keywords: 330